Economic Burden Conferred by Population-Level Cancer Screening on Resource-Limited Communities: Lessons From the ESECC Trial - Li, Fuxiao; Hu, Yanjun; Guo, Chuanhai; Lei, Liang; Li, Fenglei; Liu, Mengfei; Liu, Zhen; Pan, Yaqi; Liu, Fangfang; Liu, Ying; Hu, Zhe; Chen, Huanyu; et al. (Frontiers in Oncology, 2022)
Objectives Upper gastrointestinal (G.I.) cancer screening has been conducted in China for decades. However, the economic burden for treatment “intensively” occurred in advance due to screening in resource-limited communities remain unclear. Methods We compared the treatment costs for upper G.I. cancers from the screening and control arms of a population-based randomized trial in a high-risk area for esophageal cancer (EC) in China based on claims data from the health insurance system in the local area which included whole population coverage. Results The average out-of-pocket cost per treatment of EC in the screening arm was lower than that in the control arm (5,972 vs. 7,557). This difference was a consequence of down-staging from screening which resulted in lower cost therapy for earlier stage cancers. Moreover, this result is similar for cardial and non-cardial gastric cancer in the two study arms (7,933 vs. 10,605). However, three times as many (103 vs. 36) families in the screening arm suffered catastrophic health expenditure for all cancer types. The overall treatment cost for all EC patients in the screening arm (1,045,119) was 2.44 times that in the control arm (428,292), and the ratio for cardial and non-cardial gastric cancer was 1.12 (393,261 vs. 351,557). Conclusion Cancer treatment secondary to screening may triple the likelihood of catastrophic patient medical expenditure, and sharply increase the economic pressure on the local community, particularly for cancer types which are of high prevalence. Financial support for patients and the health insurance system should be taken into consideration when planning budgets for cancer screening programs in communities which are resource-limited.